The Impaction of Mandibular second Premolar : Extraction or Relocation? A Case Report - Ageng Wicaksono; Ida Bagus Narmada (Indonesian Journal of Dentistry, 2021)
Background: Decision to correct the Angle class I malocclusion with mandibular second premolar impaction need a special art and knowledge. The problem is what kind the treatment planning, extraction or relocation the impaction tooth. Case: A female patient, 16 years old, mesoprosopic and good proporsion of jaw with right mandibular second premolar impaction. Case Management: Treatment was initially using fixed orthodontic appliance followed by both arches expansion. Case was corected with MBT orthodontics philosopy platform. In the final treatment, molar and canine relation was obtained class I relationship, normal overjet and overbite. Conclusion: The results of this treatment indicated that mild impaction can be corrected without surgical exposure. Expantion using archwire and open coil spring is powerfull enough for this treatment. The right decision make the simplest method for the greatests results.